School-based assessment : a study on teacher's knowledge and practices - Talib, Rohaya (2014)
School-Based Assessment is a new policy venture in the highly centralized education system of Malaysia. The traditional system of assessment no longer satisfies the educational and social needs of the third millennium. In the past few decades, many countries have made profound reforms in their assessment systems. Since then, there have been only a few studies that looked into the implementation of SBA in Malaysia. Therefore, this study is conducted to investigate the knowledge and practices of Malaysian primary school teachers who directly involved in the SBA implementation. This study is deemed timely and crucial as it could provide a relevant picture for scholars, practitioners and policy makers in relation to testing and assessment. Descriptive research design was employed to examine the level of knowledge and practices of 400 school teachers in Johor Bahru that has been selected randomly using the Teacher Assessment Knowledge and Practice Inventory (TAKPI). The data were validated using Rasch Measurement Model and analyzed through descriptive and inferential statistics. Result showed that 68% from the total respondent scored was in moderate level in SBA knowledge while 75.5% of the teachers seldom applied Assessment for Learning (AfL) practices in SBA context. In regard to the result, teachers still have insufficient knowledge in implementing SBA and inconsistent on applying AfL practices. Implications on the teachers’ competency and further recommendations for future research will be discussed.